The Effect of Corporate Governance on Environmental Disclosure: The Moderating Role of Profitability - Indah Fajarini Sri Wahyuningrum; Trisni Suryarini; Fitrarena Widhi Rizkyana; Ardhana Reswari Hasna Pratista; Tihana Tyan Zahrotuddinia Tauhida (Universitas Negeri Semarang, 2025)
Purposes: Profitability proxied by Return on Assets (ROA) is used to moderating empirical indicator assessed in this analyse to assess the influence of corporate governance systems on environmental disclosure. Corporate governance is implemented through five key indicators, there are managerial ownership, foreign ownership, frequency of board of commissioners meetings, and the proportion of independent directors. The main objective of this research is to examine the link between corporate governance and sustainability reporting levels, as well as the link between environmental disclosure activities and corporate earnings.Methods: Panel data regression analysis is applied in this study through EViews version 13. The model is considered effective when applying the Random Effect Model (REM) for sample estimation. The research sample consists of 42 Publicly listed property and real estate firms on the IDX, with a total of 168 units of analysis selected through purposive sampling. The data used are secondary data obtained from annual reports and sustainability reports published by the companies during the 2021–2024 period.Findings: Profitability proxied by Return on Assets (ROA) as an indicator of financial performance efficiency, has been proven to enhance the connection between managerial control and ecological information disclosure reporting. In contrast, two other governance indicators, namely the frequency of board of commissioners meetings and the proportion of independent directors, show a positive influence on disclosure practices. However, profitability does not moderate the relationship between foreign ownership, board meeting intensity, or the extent of independent representation on the board. Meanwhile, the two forms of ownership, managerial ownership as internal control and foreign ownership as a representation of external influence, do not demonstrate a notable impact on environmental reporting policies.Novelty: This study contributes by introducing a novel approach to analyzing moderating variables through profitability. The analysis offers new insights, suggesting that the effectiveness of governance instruments in supporting environmental disclosure policies is contingent upon corporate financial results.Keywords: Environmental Disclosure, Frequency of Board of Commissioners Meetings, Foreign Ownership, Managerial Ownership, Profitability, Proportion of Independent Board Members.